Nudging is Ineffective When Attitudes Are Unsupportive: An Example from a Natural Field Experiment. Issue 4 (4th July 2021) - Dewies, Malte; Schop-Etman, Astrid; Rohde, Kirsten I. M.; Denktaş, Semiha
Abstract: For security reasons, employees of a Dutch local government department needed to wear an identifying lanyard with their employee badge, but compliance with this policy was low. Two nudges to increase compliance were evaluated in a pre-registered natural field experiment using a pre-post design, and a qualitative survey. Bayesian inference provides insufficient support for the effectiveness of the nudges. While more respondents judged the nudges and the lanyard policy positively than negatively, there was substantial negative judgment and incomprehension for both with some employees finding the nudges paternalistic. We hypothesize that the nudges were ineffective because they failed to change attitudes about the policy, and because they led to reactance among some employees. Implications for nudging within organizations are discussed.